DESKRIPSI POLA PENYEBARAN DAN FAKTOR BIOEKOLOGIS TUMBUHAN PAKU (PTERIDOPHYTA) DI KAWASAN CAGAR ALAM GUNUNG AMBANG SUB KAWASAN KABUPATEN BOLAANG MONGONDOW TIMUR - Katili, Abubakar Sidik (Sainstek, 2013)
This studi aimed to describe about the pattern and bioecology of ferns (Pteridophyta) in the sanctuary area of Ambang mountain, part of east Bolaang Mongondow district. It was a descriptive research through survey method and the data were collected through purposive sampling technique. It was divided into 5 stations; each of them 10 plots of sampling. The data were analyzed with morista index formula. The results indicated that there were 21 kinds of ferns, i.e. Asplenium nidus, Drymoglosum piloselloides, Microsorum pustulatum, Selaginella wildenowii, Adiantum peruvianum, Pyrrosia sp, Angiopteris agustifolia, Polypodium sinuosum, Lygodium sp, Dipteris conjugata, Thelypteris paleata, Davallia trichomanoides, Cyathea sp, Gleichenia linearis, Dicranopteris dichotoma, Goiophlebium persicifolium, Hymenophyllum australe, Blechnum capense, Lycopodium sp.1, Lycopodium sp.2, Dicranopteris linearis. Each of ferns gets 0 which means a clumped dissemination pattern. There ara two bioecology factor; biotic factor (habitus or subtract of pteridophyta, because beside pteridophyta terrestrial, there are pteridophyta epifit too. This petridophyta grow in body of host plant (Eucalypthus urophylla, Leucaena leucocephala, Pandanus tectoricus, Calophyllum inophyllum, Coffea arabica, Eugenia aromaticum).abiotic factor are tempherature, humidity, and light intensity.